2021
DOI: 10.1111/ecc.13548
|View full text |Cite
|
Sign up to set email alerts
|

Men's experiences of the impact of penile cancer surgery on their lives: A qualitative study

Abstract: Objective: Surgery is the primary treatment for invasive penile cancer (PC). Postoperative changes in genital anatomy and function may lead to altered body and self-image, compromised sexual function and subsequent psychological problems.The aim of this study is to describe men's experiences of the impact of PC surgical treatment on their lives. Methods:The institutional databases of two Finnish university hospitals were searched for patients who underwent surgery for invasive PC between 2009 and 2019. Of 107 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…Consequently, men after PeCa surgery have reported changes such as diminished sexual and urinary function, anxiety, depression, and alterations of body image and sexuality. [118][119][120][121][122][123][124][125][126] Multiple studies have shown that changes in appearance of the penis after surgery can diminish self-esteem and a…”
Section: Treatments Of Mental Health Complications Of Patients With Pecamentioning
confidence: 99%
See 4 more Smart Citations
“…Consequently, men after PeCa surgery have reported changes such as diminished sexual and urinary function, anxiety, depression, and alterations of body image and sexuality. [118][119][120][121][122][123][124][125][126] Multiple studies have shown that changes in appearance of the penis after surgery can diminish self-esteem and a…”
Section: Treatments Of Mental Health Complications Of Patients With Pecamentioning
confidence: 99%
“…Health Psychology Research sense of masculinity. 120,127 Because the penis is an integral part of a man's identity and sexuality, PeCa patients with significant penis tissue removal after surgery could consider reconstructive surgery to restore appearance, function, and build back self-esteem. In fact, it has been shown that PeCa patients who underwent reconstructive penis-sparing surgery had preserved penile appearance, maintained urinary and sexual function, and favorable HRQoL assessment scores.…”
Section: Mental Health In Urologic Oncologymentioning
confidence: 99%
See 3 more Smart Citations